Field performance of a semi-continuous monitor for ambient PM2.5 water-soluble inorganic ions and gases at a suburban site. (November 2016) - Young, Li-Hao; Li, Chiao-Hsin; Lin, Ming-Yeng; Hwang, Bing-Fang; Hsu, Hui-Tsung; Chen, Yu-Cheng; Jung, Chau-Ren; Chen, Kuan-Chi; Cheng, Dung-Hung; Wang, Ven-Shing; Chiang, Hung-Che; Tsai, Perng-Jy
Abstract: To reduce sampling artifacts and to improve time-resolved measurements of inorganic aerosol system, a recently commercialized semi-continuous In-situ Gas and Aerosol Composition (IGAC) monitoring system was evaluated against a reference annular denuder system (ADS; denuder/two-stage filter pack) at a suburban site over a year, during which the average PM2.5 was 37.0 ± 24.8 μg/m 3 . A suite of eight ions SO4 2−, NO3 −, Cl −, NH4 +, Na +, K +, Ca 2+ and Mg 2+ and two gases SO2 and NH3 were the target species. In comparison to the reference ADS method, the IGAC performed well in measuring the major ions SO4 2−, NO3 − and NH4 +, and the SO2 . For those species, the linear slopes, intercepts and R 2 values between the two methods all passed the performance evaluation criteria outlined by earlier similar studies. The performance of IGAC on Cl −, Na +, K + and NH3 was marginally acceptable, whereas Ca 2+ and Mg 2+ could not be properly evaluated due to the low concentrations (<0.2 μg/m 3 ) and hence inadequate amount of sample size. The ionic balance of the hourly IGAC samples averaged very close to unity, as did the daily ADS samples, though the former was considerably more variable than the latter. The overall performance of the IGAC has been shown to be comparable to other similar monitors and its improvements are discussed. Highlights: An hourly semi-continuous monitor was evaluated against an annular denuder system. Target species included eight PM2.5 water-soluble ions and two inorganic gases. Good performance for major sulfate, nitrate, ammonium ions and SO2 . Marginally acceptable performance for other minor ions and NH3 . Its performance are compared to other monitors and its improvements are discussed.